Eight-grade English textbooks evaluation in Tegal, Central Java - Raksi Hajar Prawestri (Journal of English Language and Pedagogy, 2019)
This research is aimed at measuring whether the three books used in the secondary schools in Tegal i.e â€œMandiri: Practise Your English Competenceâ€, â€œInteractive English 2â€, and â€œNew Headwayâ€ are right or not, and revealing the strength and weaknesses of the three books based on the theories of excellent textbook developed by the researcher based on the Tomlinsonâ€™s (2003) framework. This research is evaluation research. The data were collected through observation, questionnaire, and document analysis. The data were analysed using Miles, Huberman, and Saldana's flow model of qualitative data research, which includes data collection, data reduction, data display, and giving the conclusion. The study found out that â€œMandiri: Practise Your Sentence" meets only in language level criteria of excellent textbook, "Interactive English 2" all the five criteria, and "New Headway" meets three criterias. The research also found out that the strength of "Mandiri: Practise Your Sentence" relies on its language level, which is understandable and straightforward for the eighth graders. Its main weaknesses lie in the number of tests in every unit which does not cover all the skills learnt, and it does not have an excellent form of illustrations, all are too simple and uninteresting for the eighth graders. The strength of "Interactive English 2" lies in its colourful and attractive photos and cartoons that attract the students and its use of authentic text that is trendy in graphic design. Its main weakness lies in its focus on controlled practice. Meanwhile, the strength of "New Headway" comes from the attractive illustration and its use of communicative activities at the activities to make the students more creative and active in the classroom. But the main weakness lies in its sentences, which are too hard to understand for the eighth graders in Tegal.